"Invisible Burials" and Fragmentation Practices in Iron Age Europe: Excavations at the Monte Bernorio Necropolis (Northern Spain). (18th August 2021) - Torres-Martínez, Jesús F.; Fernández-Götz, Manuel; Domínguez-Solera, Santiago; Martínez-Velasco, Antxoka; Vacas-Madrid, David; Serna-Gancedo, Mariano; de la Torre, Gadea Cabanillas; Galeano, Marcos; Fernandes, Ricardo
ABSTRACT: The scarcity of burial remains in large parts of Iron Age Europe, particularly in the Atlantic regions, has often led scholars to discuss the apparent "invisibility" of graves. This paper presents the results from several excavation campaigns at Monte Bernorio, one of the most important sites of the 1st millennium b.c. on the Iberian Peninsula. The fieldwork and post-excavation work carried out in the area of the necropolis have identified numerous burial pits, with complex ritual activities characterized by fragmentation and the practice of the pars pro toto . In addition, evidence for later rituals in some of the graves can be linked to ancestor worship. The results provide important insights into funerary practices in Late Iron Age Europe, leading us to rethink the very meaning of cemeteries in the study area and beyond.